Defining a criteria for the identification of a technique for producing tomato juice - Babii, Oleksandra; Bozhko, Tetiiana; Vezhlivtseva, Svitlana; Donchevska, Raisa; Moroz, Olena; Vdovenko, Nataliia; Denysenko, Tetana; Shapovalova, Nataliia; Kepko, Valentyna (Eastern-European Journal of Enterprise Technologies, 2019)
The basis of modern analysis of the quality of juice products is a matrix approach. The essence of the matrix approach is to define a series of parameters, which comprehensively characterize the composition of juices. In this regard, it is important to study the content of individual biologically active components in addition to general quality parameters in evaluation of juices. The content of individual biologically active components depends on the origin of raw materials and technology of processing. Analysis of the chemical composition of tomatoes showed that carotenoids are characteristic nutrients inherent to this particular kind of vegetables. In this regard, we propose the content of β-carotene as the most acceptable criterion for identification. We studied quality of tomato juices by organoleptic and physical-and-chemical parameters (soluble solids content, total acidity, mass fraction of pulp and β-carotene content) in order to confirm a method of production of tomato juices, namely, the method of recovery or direct pressing. The profile analysis showed that the most positive parameters were in the juices of «EosBio» TM and «Galicia» TM, which makes us assert that their production technique was direct pressing. We established that the mass fraction of soluble solids, titratable acids and pulp met the requirements in all samples. The largest mass fraction of pulp was in the juices of «Galicia» TM – 30.80 and «EosBio» TM – 24.23. This data confirms that the method of production of these juices was direct pressing. We established that the content of β-carotene in the juices of «Sandora» TM, «Rich» TM and «Sadochok» TM produced by the method of recovery was in the range of 0.24–0.32 mg/100 g. At the same time, these values were significantly higher in the juices of «Galicia» TM and «EosBio» TM produced by the method of direct pressing, they were 0.589 and 0.591 mg/100 g, respectively. Thus, we confirmed the assumption about the connection between a production method and the content of β-carotene in tomato juices. We proposed using this parameter as a marker criterion for the identification of a technique for producing tomato juices